PINK1-mediated phosphorylation of LETM1 regulates mitochondrial calcium transport and protects neurons against mitochondrial stress. Issue 1 (December 2017) - Huang, En; Qu, Dianbo; Huang, Tianwen; Rizzi, Nicoletta; Boonying, Wassamon; Krolak, Dorothy; Ciana, Paolo; Woulfe, John; Klein, Christine; Slack, Ruth; Figeys, Daniel; Park, David
Abstract Mutations in PTEN-induced kinase 1 (PINK1) result in a recessive familial form of Parkinson's disease (PD). PINK1 loss is associated with mitochondrial Ca2+ mishandling, mitochondrial dysfunction, as well as increased neuronal vulnerability. Here we demonstrate that PINK1 directly interacts with and phosphorylates LETM1 at Thr192 in vitro. Phosphorylated LETM1 or the phospho-mimetic LETM1-T192E increase calcium release in artificial liposomes and facilitates calcium transport in intact mitochondria. Expression of LETM1-T192E but not LETM1-wild type (WT) rescues mitochondrial calcium mishandling in PINK1-deficient neurons. Expression of both LETM1-WT and LETM1-T192E protects neurons against MPP+ –MPTP-induced neuronal death in PINK1 WT neurons, whereas only LETM1-T192E protects neurons under conditions of PINK1 loss. Our findings delineate a mechanism by which PINK1 regulates mitochondrial Ca2+ level through LETM1 and suggest a model by which PINK1 loss leads to deficient phosphorylation of LETM1 and impaired mitochondrial Ca2+ transport.. Mutations in the mitochondrial kinase PINK1 result in familial Parkinson's disease. Here the authors show that LETM1, a mitochondrial inner membrane protein, is a substrate of PINK1 that regulates Ca2+ handling in mitochondria in response to mitochondrial toxins.